Hubungan Antara Regulasi Diri dan Perencanaan Karir pada Remaja Putri Bali - Istriyanti, Ni Luh Arick; Simarmata, Nicholas (Jurnal Psikologi Udayana, 2014)
Adolescences have many developmental tasks. Some of them are getting involved into social role and capable of doing a proper career planning. When adolescences are faced by the strict culture, like Balinese Teenage Girls who involved into sekaa teruna organization, they have to actively participate in every cultural activity as a part of social role, and also doing career planning for their future’s preparation. In doing career planning, adolescences need the ability to manage their potential and retrieved information without ignoring their social roles. Therefore, Balinese Teenage Girls need to find the right way to do career planning and fulfill their social roles that are have a good self-regulation. Because of that researcher assumed that there is a positive relationship between self-regulation and career planning of Balinese Teenage Girls.   This research method is quantitative-correlation, using 135 subjects that are Balinese Teenage Girls who joined sekaa teruna organization in Badung and their age ranges from 15-20 years old. Method used for collecting the data is questionnaire which is self-regulation scale and career planning scale. The reliability of self-regulation variable is 0.916 and for the career planning variable is 0.911. The normality of self-regulation variable is 0.098 and for the career planning variable is 0.269. The linearity between self-regulation variable and career planning variable is 0.000. The determination coefficient is 0.354. The analysis method is Pearson product moment correlation techniques. The correlation coefficient is 0.595 with 0.000 probabilities. It is proved there is a positive relationship between self-regulation and career planning of Balinese Teenage Girls.   Keywords: Self-Regulation, Career Planning, Balinese Teenage Girls